The Role of Santri Entrepreneurship and Santri Business Activities in Economic Independence (Case Study at Manahijul Huda Islamic Boarding School) - Muhammad Irfan Sholehudin; Taryono Taryono; Muhamad Nurman (Universitas KH. Abdul Chalim Mojokerto, 2025)
Many previous studies have explored business management in Islamic boarding schools as the research location object. The author is interested in studying this topic because the research results are expected to contribute to the development of business management research in Indonesia. This research discusses the role of entrepreneurial students in building economic independence at Manahijul Huda Islamic Boarding School. This pesantren (Islamic boarding school) develops various business units, such as a café, cooperative, hydroponic farming, laundry, and barbershop, which are directly managed by the students. This research uses a qualitative method with a case study approach. Data were collected through participatory observation, semi-structured interviews, and documentation. The research results show that the entrepreneurship of the students has a significant impact on the economic sustainability of the pesantren. The profits from the business units are used for the construction and development of the pesantren without relying on external donations. In addition, this program instills an entrepreneurial spirit in the students, trains their creativity, and develops Sharia-based business skills. The implementation of entrepreneurship also creates job opportunities for the surrounding community, thereby supporting local economic welfare. The success of this model proves that pesantren not only play a role in religious education but also in the economic empowerment of students and the community. With the right strategy, pesantren can become independent and competitive institutions without neglecting Islamic values. This research recommends the development of digital businesses, optimization of technology-based marketing, and collaboration with external institutions to enhance the competitiveness and sustainability of pesantren businesses in the modern era.